CAIR SEBAGAI KONSEP DESAIN INTERIOR RESTORAN TIMOR RAYA KOTA KUPANG - Lily, Budhi B. (Universitas Atma Jaya Yogyakarta, 2015)
Abstract: Timor Raya Restaurant comes from the proliferation of places that offer rental services of wedding packages in the city. The initial function of this restaurant was a venue for weddings with supported interior concept. As the time goes by, the restaurant also rented out for other events such as birthdays, graduations, meetings and gathering severance and other events that makes the interior concept incompatible anymore with such events. Flexibility ofÂ the interior space is the main problem of this restaurant and to study about it can use the